Social Incentives Anticipation and Consummation: Investigating Neural Activity in Women Using Methamphetamine - Wei, Shuguang; Zou, Zilan; Xue, Zhaoxia; Cao, Siqi; Yu, Hao; Han, Jie; Wang, Haiyan; Wu, Haiyan; Liu, Xun (Frontiers in Psychology, 2020)
Individuals with methamphetamine use disorder are considered to have enhanced reactivity to rewards or drug cues. However, whether this holds true in the social incentives processing is still unclear. The current study investigated the electroencephalographical (EEG) evidence of social incentives processing in women with methamphetamine use disorder (MA group, n = 19) and in a healthy control group (HC group, n = 20) using social incentive-delay (SID) tasks. In the SID, participants received a “Like” (e.g., thumbs-up) or “Unlike” (e.g., thumbs-down) from WeChat emojis as social incentives, or neutral feedback. During the anticipation stage, the cue-P3 and stimulus-preceding negativity (SPN) was larger for the social incentives condition than for the neutral condition. During the consummation stage, the FRN (feedback-related negativity) was marginally significantly larger in the HC group than the MA group for the social incentive condition, whereas there was no significant difference between the groups for neutral condition. Interestingly, the FB-P3 was larger for social positive feedback than for social negative feedback in the MA group, but not in HC group. Furthermore, only the HC group showed significant positive correlation between the anticipatory event-related brain potential (ERP, such as cue-P3) and the consummatory ERP (FB-P3) in the social incentive condition. The findings suggest that women with MA use disorder have a blunted neural response to the processing of social incentives and a blunted neural response to negative social feedback, which helps to elucidate the neural mechanisms of social incentives processing in individuals with MA use disorder.